Coastal Vulnerability Study on Potential Impact of Tsunami and Community Resilience in Pacitan Bay East Java - Zainul Hidayah; Nur Nazilatul Rohmah; Maulinna Kusumo Wardhani (Universitas Muhammadiyah Surakarta, 2022)
Collisions or harsh shifting of earth plates accompanied by an earthquake in the ocean would pose a potential tsunami. The coastal area in Pacitan Bay East Java faces directly to the Indian Ocean and is prone to tsunami disasters. This study aims to determine the vulnerability level of the area and the resilience of coastal communities against tsunamis. The geographic Information System (GIS) method was used in this study. This study applied weighted overlay calculation with four components: elevation, slope, and distance from the beach and the river to measure the vulnerability level. Moreover, Coastal Community Resilience (CCR) method was applied to measure the predictive response of the communities. The results indicated that most of the area in Pacitan Bay (79,70%) was categorised into high to very high vulnerable against tsunamis. The CCR results showed the low index structure design and post-disaster recovery elements.